Chitosan impregnated gutta-percha points: antimicrobial in vitro evaluation and mechanical properties. Issue 9 (13th June 2019) - Cardelle-Cobas, Alejandra; Reis, Patrícia J. M.; Costa, Eduardo; Tavaria, Freni K.; Pintado, Manuela E.
Abstract: Chitosan-impregnated gutta-percha points (ChitGPP) were tested for their ability to inhibit the growth of microorganisms usually involved in root canal infections. Their mechanical properties were also studied and compared with the commonly used commercial points in endodontics. ChitGPP were more efficient in reducing the microbial load than those without chitosan. ChitGPP also possess better tensile and elastic properties than commercial ones. After six months of storage, ChitGPP's were still able to reduce the bacterial load by 1 log, suggesting that impregnation of gutta-percha points with chitosan could be a good alternative to obtain gutta-percha points with improved antimicrobial properties. Graphical Abstract: